STRATEGI GURU MENINGKATKAN MINAT BELAJAR SISWADALAM PROSES PEMBELAJARAN MATA PELAJARAN SENI BUDAYA DAN PRAKARYA DI KELAS VA MIS AT-TAQWA SAMBAS TAHUNPELAJARAN 2023-2024 - Paris Paris; Eliyah Eliyah; Mauizatul Hasanah (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The purpose of this study is to describe and analyze: 1) Student learning interest in arts, culture, and crafts at At-Taqwa Islamic Junior High School, Sambas, in the 2023-2024 academic year; 2) Teacher strategies for increasing student learning interest in Arts, Culture, and Crafts at At-Taqwa Islamic Junior High School, Sambas, during the 2023-2024 academic year; 3) Factors influencing teachers in increasing student learning interest in arts, culture, and crafts at At-Taqwa Islamic Junior High School, Sambas, in the 2023-2024 academic year. This study employed a qualitative approach and phenomenological research. Data collection techniques included interviews, observation, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was verified using source triangulation, technical triangulation, and member checking. The results of this study indicate that: (1) Students' interest in learning is driven by individual and social motives, group work learning methods, collaborative projects and emotional factors influence students' interest in learning, (2) Teacher strategies to increase interest in learning are strategies implemented by role playing, presentations in class and expository strategies, (3) Factors that influence teachers to increase students' interest in learning are internal factors, namely from within themselves, including psychological aspects consisting of student motivation, external factors, namely from outside, including social environmental factors and non-social factors consisting of schools and classmates can influence teachers to increase students' interest in learning.